Factors associated with uncomplicated prolonged neonatal jaundice in term Malay infants : a case control study - Zahedi, Nor Amirah Ahmad (2020)
Aim: To determine factors associated with uncomplicated prolonged neonatal jaundice in Malay term infants. Methods: A case-control study was conducted in 120 prolonged neonatal jaundice infants and 120 healthy control infants, in a pediatric clinic of a tertiary center between February 2018 and September 2018. Cases were selected from specialized prolonged jaundice clinic while, controls were healthy infants conveniently selected from neonatal clinic. Data was gathered from caretaker interviews, home-based vaccination records, and attending physician records. Regression analysis was performed to determine the independent associated factors of prolonged unconjugated jaundice. Results: Hundred and twenty infants with prolonged unconjugated jaundice was analyzed in this study, of which 44.2% jaundice had resolved upon reviewed at 31 days of life. Cases and control age between 2 weeks to 8 weeks. Univariate analysis demonstrated potentialassociations observed in maternal history of gestational diabetes mellitus, maternal intrapartum usage of oxytocin,vaginal versus caesarian delivery,SGA versus AGA birth weight babies, G6PD deficiency,congenital hypothyroidism, and exclusive breastfeeding versus mixed feeding. G6PD deficiency was a predicted risk factor(adjusted OR 5.3 CI 1.02-28.20) for prolonged jaundice with unexpected negative association of congenital hypothyroidism(adjusted OR 0.057 95% CI 0.01-0.72), infant of maternal gestational diabetes mellitus(adjusted OR 0.31 95% CI 0.15-0.65), and SGA birth weight (adjusted OR 0.20 95% CI 0.10-0.396). Conclusion: This study demonstrates positive relationship between G6PD deficiency and prolonged unconjugated jaundice. However, maternal history gestational diabetes mellitus, congenital hypothyroidism and SGA birth weight were protective factors for prolonged unconjugated jaundice in our population.